Tantangan dan Gagasan Desain Asesmen Terpadu untuk Penanganan Penyalahguna Narkotika di Indonesia - Febri Handayani; Lysa Angrayni (Jurnal Penelitian Hukum De Jure, 2024)
Integrated Assessment challenges for handling narcotics abuse include; Narcotics regulation is still debating between a criminal approach and a health approach, this will be related to the request for an assessment from TAT. Integrated assessment becomes a new legal problem if the recommendation procedure is carried out unfairly. Challenges in the coordination function between agencies/institutions. The design idea for an Integrated Assessment for handling narcotics abusers is; availability of government-owned rehabilitation homes in every district/city area, optimization of submission of assessments by investigators to TAT to obtain assessment results in every narcotics case, as well as legalization of integrated assessment norms. The recommendation is that investigators in narcotics cases must submit an assessment request to the TAT as an initial assessment mechanism because it is a guarantee of legal certainty that must be realized if the legalization of norms regarding integrated assessment has been carried out.